2012
DOI: 10.2147/iprp.s36328
|View full text |Cite
|
Sign up to set email alerts
|

Can a community pharmacy sleep assessment tool aid the identification of patients at risk of sleep disorders in the community: a pilot study

Abstract: Background: When experiencing sleep problems for the first time, consumers may often approach community pharmacists for advice as they are easily accessible health care professionals in the community. In Australian community pharmacies there are no specific tools available for use by pharmacists to assist with the assessment and handling of consumers with sleep enquiries. Objective: To assess the feasibility of improving the detection of sleep disorders within the community through the pilot of a newly develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The findings of the study supports the assumption that the community pharmacies in Pakistan have converted into places of medical practice, carried out by untrained dispensers. Similar findings were reported by an Australian study which highlighted that when over the counter pharmacist-only sleep medication (Restavit) was requested in the Australian community pharmacy setting, only 30% of requests were handled entirely by the pharmacist 26. The results of the study highlighted that benzodiazepines were the most commonly given drugs and most of the remedies suggested by the dispensers were in brand names.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The findings of the study supports the assumption that the community pharmacies in Pakistan have converted into places of medical practice, carried out by untrained dispensers. Similar findings were reported by an Australian study which highlighted that when over the counter pharmacist-only sleep medication (Restavit) was requested in the Australian community pharmacy setting, only 30% of requests were handled entirely by the pharmacist 26. The results of the study highlighted that benzodiazepines were the most commonly given drugs and most of the remedies suggested by the dispensers were in brand names.…”
Section: Discussionsupporting
confidence: 84%
“…This might be due to low availability of qualified personnel at community pharmacies. Similar results of low history taking and counseling practices for insomnia was reported 26,29. However, the findings of the present study showed that pharmacists were more frequently involved in the process of history taking but their presence was negligible at community pharmacies.…”
Section: Discussionsupporting
confidence: 81%
“…A Swiss study which screened pharmacy customers to detect the likelihood of any sleep problem or daytime sleepiness based on the answers from online questionnaires found that 32% customers were suspected of having a disorder in at least one category of sleep disorders and 20.7% were suspected of having excessive daytime sleepiness [10]. Kashyap et al (2012) screened 241 community pharmacy customers in a survey over a 4-week period and found that among the participants, 50.2% were regular snorers and 30.7%, 10.7% and 7.9% were at risk of insomnia, daytime sleepiness and obstructive sleep apnoea respectively [11]. Even though sleep disorders are highly prevalent in the community, they still remain under-diagnosed and inadequately treated [10].…”
Section: Introductionmentioning
confidence: 99%
“…Even though sleep disorders are highly prevalent in the community, they still remain under-diagnosed and inadequately treated [10]. Assessing and monitoring sleep [10,11] is the first step in preventing and treating the condition therefore appropriate validated measuring tools are essential. Assessment is also required to assess the quality and quantity of sleep following any treatment, particularly at home.…”
Section: Introductionmentioning
confidence: 99%
“…An Australian study demonstrated that Community Pharmacy Sleep Assessment Tool (CPSAT) may serve as a practical tool for the identification of patients at the risk of developing sleep disorders within the community. 13 The aforementioned study was the pioneer among the pharmacy-administered studies to develop a standardized questionnaire or scale for the assessment of sleep disorder risk in the community. This provided an opportunity, from the CP's perspective, to diagnose OSA and refer the suspected OSA candidates to FPs for the confirmation of the diagnosis.…”
mentioning
confidence: 99%